Tahlīl al-Akhṭā’ al-Dalāliyah fī Kitābah al-Risālah al-ʿIlmiah min Nāhiyah al-Uslūb wa al-Mu’jam - Anisatin, Luthfi; Salma, Salma (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2024)
A thesis is a scientific paper based on the research results of final undergraduate (S1) students. The thesis paper must contain new and valuable information written in good and correct language. However, the fact is that there are still many errors found in writing student thesis papers, especially in Arabic, so that these errors are increasingly significant and often leave an impact on the meaning indications in various writings. The aim of this research is to mention and classify semantic errors in Arabic thesis papers, correct semantic errors mentioned in thesis papers, and analyze the factors that cause students to make mistakes in thesis papers. The approach used is descriptive qualitative, which describes semantic errors in the thesis paper. The analytical method used is data collection and analysis. Based on the research results, it was found that there were still many students' mistakes in their thesis papers, especially in aspects of language style and in terms of language accuracy based on dictionaries. Apart from that, there are many reductions and additions of words which cause meanings that are difficult for readers to understand. The factors causing errors are influenced by the mother tongue, lack of grammatical mastery, lack of vocabulary mastery and the use of Google Translate which is often used in translation.